2013
DOI: 10.1111/tbed.12130
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the Antibody Response to Foot-and-Mouth Disease Primo-vaccinated Calves

Abstract: Foot-and-mouth disease (FMD) vaccines are routinely used as effective control tools in large regions worldwide and to limit outbreaks during epidemics. Vaccine-induced protection in cattle has been largely correlated with the FMD virus (FMDV)-specific antibodies. Genetic control of cattle immune adaptive responses has been demonstrated only for peptide antigens derived from FMDV structural proteins. Here, we quantify the heterogeneity in the antibody response of cattle primo-vaccinated against FMD and study it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Greater bacterial killing and neutrophil oxidative burst activity, were also observed in the whole blood from the post-weaned Holstein calves, following incubation with Escherichia coli [ 15 ]. Furthermore, calves from J sires had lower total anti-foot-and-mouth disease virus serum antibody titres, in response to three different vaccine strains, than calves from Holstein sires suggesting that the genetic background of calves influences humeral immune responses [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Greater bacterial killing and neutrophil oxidative burst activity, were also observed in the whole blood from the post-weaned Holstein calves, following incubation with Escherichia coli [ 15 ]. Furthermore, calves from J sires had lower total anti-foot-and-mouth disease virus serum antibody titres, in response to three different vaccine strains, than calves from Holstein sires suggesting that the genetic background of calves influences humeral immune responses [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite widespread adoption of vaccination protocols in the beef cattle industry, BRDC remains extremely prevalent due to varying levels of vaccine efficacy [5, 6]. Research into response to vaccination has identified multiple environmental and management variables which impact an individual calf’s ability to mount an antibody response [79]. Factors such as maternally derived antibody levels from colostrum, calf age, seasonality, and weaning status all impact a calf’s individual immune system, and result in variability in its response to vaccination [1012].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the BCG (Bacillus Calmette–Guérin) vaccine provides a wide range of protection against tuberculosis in humans, ranging from nearly ineffective to nearly completely effective (1, 2). Vaccination of pigs against foot and mouth disease virus (FMDV) is characterized by significant animal-to-animal variation in anti-FMDV IgA (3); and post-vaccination anti-FMDV antibody responses in cattle are significantly affected by genetic background (4). Furthermore in swine there is substantial antibody response variation to vaccination against Actinobacillus pleuropneumoniae and to infection with Mycoplasma hyorhinis (5, 6).…”
Section: Introductionmentioning
confidence: 99%